Optimization of the performance of an automated/continuous pilot scale soymilk plant for medium and small‐scale entrepreneurs. Issue 12 (6th September 2022) - Mangaraj, Shukadev; Sharma, Veer Mohan; Nishad, Praween; Thakur, Rajeev R.
Abstract: The manual operations involved in the existing batch type soymilk plant reduces the overall capacity and quality of soymilk of the plant and due to which, its commercial application is limited. Therefore, the objective of this research work was to optimize the performance of a continuous soymilk extraction plant by maximizing the capacity and protein content while minimizing the hydroperoxide content through the manipulation of feed rate (kg/h), cooker temperature, cooker pressure, and holding time. Four independent variables namely; feed rate (10–20 kg/h), cooker temperature (100–120°C), cooker pressure (1.5–2.5 kg/m 3 ), and holding time (3–7 min) were selected for testing the developed plant. The selected parameters were optimized and, the optimum value of feed rate, cooker temperature, cooker pressure, and holding time was obtained as 19.83 kg/h, 110°C, 2.44 kg/cm 2 and 3 min, respectively. The corresponding values of responses, that is, the capacity, protein content and hydroperoxide level, were 98.58 L/h, 3.15%, and 5.36 mol/g, respectively. Novelty impact statement: The developed pilot scale continuous type soymilk plant has successfully adopted and run by a number of self‐help group at medium and small scale enterprises. The output capacity and quality of soymilk produced by the plant were highly appreciated by the consumers. This development has the potential to create a golden opportunity of employment and income generation for the rural youth to initiate a new start up for running their own business and to support the vocal for local as well as self‐reliance India initiative of the Govt. of India.